Experience of using Beers criteria in clinical practice (according to Russian literature) - M. S. Cherniaeva; M. A. Rozhkova; M. V. Kazakova; L. A. Egorova; O. M. Maslennikova; G. S. Lebedev; N. V. Lomakin; D. A. Sychev (Фармакоэкономика)
Objective: analysis of domestic scientific literature to identify ways of applying the Beers criteria, frequency of prescriptions and the structure of potentially inappropriate medications (PIMs) in elderly patients.Material and methods. The search for publications was carried out in Google Scholar abstract database, as wel as in eLibrary and CyberLeninka information-bearing networks for the period from 2013 to 2023. In total, 34 articles were found, among which 18 sources used Beers criteria as a tool for identifying PIMs.Results. In inpatient therapeutic departments, the maximum frequency of PIMs prescriptions according to the Beers criteria was 66.6% of cases, in surgical departments – 70%, in psychiatric departments – 90.4%, and in outpatient treatment settings – 28%. Non-steroidal anti-inflammatory drugs at different diseases were the most prescribed group of PIMs in both inpatients and outpatients. Surgical hospitals took the leading position in prescribing these drugs; specifically, more than 2/3 of elderly patients (75%) received them. According to two studies describing clinical cases of drug-induced falls in patients, the Beers criteria were effective in identifying drugs that can provoke this condition. One of papers presented application of Beers criteria to assess the economic affordability of replacing PIMs with safer new generation drugs.Conclusion. An analysis of domestic literature data has shown various ways of applying the Beers criteria, the frequency of prescriptions, and the most common PIMs. This information will help healthcare workers to be more wary of such drugs and think over applying the Beers criteria in routine practice of geriatric patients, which will further prevent or reduce the number of adverse drug reactions.